2010
DOI: 10.1111/j.1365-263x.2010.01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and oral hygiene intervention in secondary school pupils

Abstract: The 1-year dietary intervention was long enough to show improvement in eating habits and in habits for quenching thirst, and some decrease in the LF values of molars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 9 publications
1
21
1
Order By: Relevance
“…Despite this positive present situation, the common use of sweet snacks may contribute to an increase in the use of sugary beverages in future . Males have been shown to consume sweet snacks and sugary beverages more often than females in several studies , but also opposite results have been resulted from neighbouring countries to DPRK in China and in Japan . In this study, there were only minimal gender differences in the use of sweet snacks and sugary beverages.…”
Section: Discussioncontrasting
confidence: 65%
“…Despite this positive present situation, the common use of sweet snacks may contribute to an increase in the use of sugary beverages in future . Males have been shown to consume sweet snacks and sugary beverages more often than females in several studies , but also opposite results have been resulted from neighbouring countries to DPRK in China and in Japan . In this study, there were only minimal gender differences in the use of sweet snacks and sugary beverages.…”
Section: Discussioncontrasting
confidence: 65%
“…The characteristics of the studies can be found in Table , which depicts the included studies’ the general characteristics. Among the 12 included studies, six were randomized by school, two by classroom and four by individuals …”
Section: Resultsmentioning
confidence: 99%
“…Anttonen assessed the effect of the actions of OHE on the monitoring of demineralization and remineralization of tooth surfaces, based on mean laser fluorescence values and concluded that the 1‐year OHE was resulted in favourable changes in dietary habits and a decrease in the laser fluorescence values of molars. The results of the study were presented in graphs and the type of measurement for caries condition, precluded its inclusion in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The success of these measures has been reported by numerous studies using different outcomes. Most studies reported a significant improvement in schoolchildren's knowledge, oral behaviour, and oral status after oral education sessions were performed over the long-term [Tai et al, 2009;Anttonen et al, 2011;Amalia et al, 2012;Esan et al, 2015;Petersen et al, 2015;Lai et al, 2016]. Esan et al [2015] reported that a 4-year school-based oral health education programme increased the number of children using fluoride toothpaste and those brushing twice daily, and decreased children's consumption of sweets.…”
mentioning
confidence: 99%
“…Schools were encouraged to have a policy regarding their children's oral health and to subsequently establish oral health-related activities or environments in schools. Studies on oral health-promoting schools were conducted in many countries, such as Indonesia, Taiwan, China, New Zealand, Nigeria, Finland, and Thailand [Petersen et al, 2001[Petersen et al, , 2004[Petersen et al, , 2015Tai et al, 2009;Anttonen et al, 2011;Amalia et al, 2012;Esan et al, 2015;Lai et al, 2016;Thornley et al, 2017]. Examples of the oral health supportive activities or environments established in schools were oral health education taught by professionals, oral health education integrated into the school curriculum and taught by school teachers, simple oral examinations conducted by teachers, toothbrushing after lunch, free toothbrushes and toothpaste (toothbrushing materials) for children, restricting sugary and junk food in schools, and providing vegetables and fruit in school meals [Kwan et al, 2005].…”
mentioning
confidence: 99%